Prevalence of the Double Burden of Malnutrition among Adolescents: Associations with Lifestyle Behaviors and Clusters of Social Determinants - Raytta Silva Viana; Marcus Vinicius Nascimento-Ferreira; Beatriz D. Schaan; Katia Vergetti Bloch; Kênia Mara Baiocchi de Carvalho; Felipe Vogt Cureau; Augusto César Ferreira De Moraes (MDPI AG, 2024)
The double burden of malnutrition (DBM) is a condition in which malnutrition coexists with overweight, reflecting a new layer of malnutrition. Our objectives were to assess prevalence; test associations between DBM and 24-hour movement behaviors; and investigate whether DBM is associated with clusters of social determinants. Methods: This multicenter cross-sectional study included 1152 adolescents (12 to 17 years old) from four Brazilian cities. Body mass index (BMI, kg/m2) was used to estimate overweight, and the adopted cutoff points took into account the curves established for age and sex: Z-score > 1 and ≤2 (overweight) and Z-score > 2 (obesity). The serum concentration of 25-hydroxyvitamin D [25(OH)D] was stratified into three levels: vitamin D deficiency ≤ 20 ng/mL; vitamin D insufficiency = 21-29 ng/mL; optimal vitamin D ≥ 30 ng/mL. We used multilevel Poisson regression models to estimate prevalence ratios (PRs) and their respective 95% confidence intervals (95%CI) and to analyze the association between DBM and covariates. A significance level of p < 0.05 was considered. Cluster analyses were performed by applying a combination of hierarchical and non-hierarchical methods. Results: A population prevalence of DBM of 7.3% (95% CI: 5.9-8.9) was revealed. A percentage of 19.2% (95% CI: 17.0-21.6) of adolescents were overweight, and 8.3% (95% CI: 6.8-10.1) were obese. A total of 41.5% (95% CI: 38.7-44.4) had vitamin D deficiency, and 25.8% (95% CI: 23.4-28.4) had vitamin D insufficiency. However, 24-hour movement behaviors were not associated with DBM. Adolescents living in the southern region of the country, from public schools whose mothers have higher education, have a 1.94 [PR = 2.94 (95% CI: 1.20-7.23)] times greater chance of developing DBM. These results highlight the importance of specific factors to improve the nutritional health of adolescents, considering the specific social determinants identified in this study.